Heptavalent symmetric graphs of order 18p - Guo, Song-Tao; Wang, Li (Utilitas Mathematica, 2018)
A graph is symmetric if its automorphism group acts transitively on the set of arcs of the graph. In this paper, we classify connected heptavalent symmetric graphs of order 18p for each prime p. As a result, there are two sporadic such graphs for each p = 2 and 5. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.